Asymilacje pod względem dźwięczności w grupach spółgłoskowych w polszczyźnie XVI i pierwszej połowy XVII wieku (na podstawie druków krakowskich) - Pyrkosz, Anna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
The aim of the article is to present the problem of assimilation with reference to tone within consonant groups (inside words and at word boundaries) in the Polish language of the 16th century and the first half of the 17th century. Research material is analysed in three synchronic sections, making it possible to capture the dynamics of change. On the basis of the collected material, general tendencies have been determined for particular periods and dominants with reference to orthography of consonant groups, which are compared with individual orthographic solutions applied by individual publishing houses. It was possible to conclude from the results of the studies that tonal assimilations did not belong, during the analysed period, to mass phenomena, although their examples can be found in every text. Moreover, noticeable is the tendency to limit the variant character of records concerning heterogeneous consonant groups, which is expressed by the decline in the number of assimilated forms in the subsequent study periods.